Elexacaftor-Tezacaftor-Ivacaftor: A Life-Changing Triple Combination of CFTR Modulator Drugs for Cystic Fibrosis - Mafalda Bacalhau; Mariana Camargo; Grace A. V. Magalhães-Ghiotto; Sybelle Drumond; Carlos Henrique M. Castelletti; Miquéias Lopes-Pacheco (MDPI AG, 2023)
Cystic fibrosis (CF) is a potentially fatal monogenic disease that causes a progressive multisystemic pathology. Over the last decade, the introduction of CF transmembrane conductance regulator (CFTR) modulator drugs into clinical practice has profoundly modified the lives of many people with CF (PwCF) by targeting the fundamental cause of the disease. These drugs consist of the potentiator ivacaftor (VX-770) and the correctors lumacaftor (VX-809), tezacaftor (VX-661), and elexacaftor (VX-445). In particular, the triple combination of CFTR modulators composed of elexacaftor, tezacaftor, and ivacaftor (ETI) represents a life-changing therapy for the majority of PwCF worldwide. A growing number of clinical studies have demonstrated the safety and efficacy of ETI therapy in both short- and long-term (up to two years of follow-up to date) and its ability to significantly reduce pulmonary and gastrointestinal manifestations, sweat chloride concentration, exocrine pancreatic dysfunction, and infertility/subfertility, among other disease signs and symptoms. Nevertheless, ETI therapy-related adverse effects have also been reported, and close monitoring by a multidisciplinary healthcare team remains vital. This review aims to address and discuss the major therapeutic benefits and adverse effects reported by the clinical use of ETI therapy for PwCF.